Розмежування правових реалій у процесі творення кримінально-правових норм (огляд сучасних наукових сентенцій) - Яцишин, Михайло Михайлович; Yatsyshyn, M. (Східноєвроп. нац. ун-т ім. Лесі Українки, 2013)
Статтю присвячено аналізу наукових підходів до з’ясування правової реальності в процесі творення кри- мінально-правових норм. Наявна система виконання кримінальних покарань та попереднього ув’язнення не відповідає сучасному рівню розвитку суспільства й держави, а також задекларованим принципам поваги до прав і свобод людини в процесі виконання покарань. Тому питання формування державної політики в цій сфері набуває першочергової ваги.The article is devoted to the analysis of the scientific approach towards finding out legal reality in the criminal law making process. The current system of execution of criminal sentences and pre-trial detention does not meet the current level of development of society and the state, as well as the declared principles of respect for human rights and freedoms in the penitentiary process. Therefore the question of public policy in this area is of primary importance. Today, the scientific community intensified search for a rational solution of pressing problems. Creation of criminal law norms in the broadest sense, appears as a complex system involving in essence, meaning, purpose and objectives set laws and applicable international treaties that govern this area of public relations.
Differentiation of Legal Realities in the Criminal Law Norms Making Process (Overview of Current Scientific Maxim).
Keywords: правова реальність; кримінально-правова норма; нормативно-правовий акт; покарання; legal reality; criminal law; the legal act; punishment